Characterization oí wild perennial ryegrass populations from Galicia (Spain) - Oliveira Prendes, J.A.; Charmet, G. (Pastos, 2011)
Forty seven spontaneous populations of perennial ryegrass were collected as seeds in 1985 en Galicia (North-West Spain), and evaluated at Investigaciones Agrarias Galicia Station, near ha Coruña, in a spaced plañís nursery. Twelve agronomic traits were scored since 1986 to 1988. Indigenous populations show, on average, poorer agronomic performance than control cultivars. Since they have much wider range of variation, the hest ones can he as good as commercial Unes for some traits. A principal component analysis has heen used to summarize the data from population means and a hierarchical clustering method using Euclidean standardized distance has heen performed. This classification leads to a partition into 4 clusters, one of them grouping the most interesting populations. It is noticeahle that cv «Brigantia», which was constructed hy mass selection from a luild population from La Coruña, appears to he the hest of the control ivhen tested in Galicia. A factorial discriminant analysis was then carried out using ecological (climate, soil) data from the collection sites. This analy- sis succeeded in founding linear combinations of ecological traits which discrimínate the clusters established from agronomic traits only. The implications jor genetic resources management and genetic improvement are di s cus sed